1997
DOI: 10.1523/jneurosci.17-22-08842.1997
|View full text |Cite
|
Sign up to set email alerts
|

Social Stress in Hamsters: Defeat Activates Specific Neurocircuits within the Brain

Abstract: During an agonistic encounter, subordinate male hamsters display defensive and submissive postures and show increased secretion of glucocorticoids, whereas dominant males do not. To determine whether specific neuronal pathways are activated during the behavioral and neuroendocrine responses of subordinate males, expression of c-fos mRNA within the brains of subordinate males was compared with the pattern in dominant males after fighting. After 1 week of handling, pairs of hamsters were either swapped between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
149
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(166 citation statements)
references
References 58 publications
8
149
0
7
Order By: Relevance
“…The boundaries of the brain areas were identified using adjacent Nissl-stained sections. A template or outline was developed for each brain nucleus or subnucleus based on the shape and the size of the region (Kollack-Walker et al, 1997). The location and relative size of each template are illustrated in Figure 2.…”
Section: Cell Counting and Statistical Analysismentioning
confidence: 99%
“…The boundaries of the brain areas were identified using adjacent Nissl-stained sections. A template or outline was developed for each brain nucleus or subnucleus based on the shape and the size of the region (Kollack-Walker et al, 1997). The location and relative size of each template are illustrated in Figure 2.…”
Section: Cell Counting and Statistical Analysismentioning
confidence: 99%
“…Furthermore, psychosocial stressors are known to precipitate stress-induced psychopathology (Dunner et al, 1979;Hammen et al, 1992). Therefore, when performing preclinical studies to understand mechanisms relevant to human psychopathology, it is important to use species-specific psychosocial stressors (Albeck et al, 1997;Kollack-Walker et al, 1997;Blanchard et al, 1998). Exposure of rats to a natural predator such as a ferret represents a potent form of psychosocial stress.…”
Section: Introductionmentioning
confidence: 99%
“…Dramatic increases in transcriptional activity in the PAG during dominant/submissive encounters have been observed. In hamsters, agonistic encounters between dominant and submissive animals produce increased fos-immunolabeled neurons in the dorsolateral columns of the PAG in the subordinate animals [40]. In addition, recent studies in the rat demonstrated that excitation of the lateral PAG produced largely defensive responses, including emission of 22-kHz distress ultrasonic vocalizations (USVs).…”
Section: Introductionmentioning
confidence: 99%